PENGUATAN TIGA PILAR PENDIDIKAN DI ERA GLOBALISASI - Efrizal Nasution (DIALEKTIKA, 2018)
This paper discuss abaut the reinforcement threepillars of education in the era of globalization. Education really can’t be passed on to the school, but must besupported by role as well as parents and the community. This is a pre condition in the increase in fairly education in school. Then te third pillar of education should be more reinforced role to play, because in principle the education is the responsibility together